PENGARUH LINGKUNGAN BELAJAR DI SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DI SMK NEGERI 1 PONTIANAK - Disty, Fanesa; Nuraini, Nuraini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe goal of this research was to investigate the extent of the influencebetween the learning environtment at school toward the year-11 students learning motivation at "SMKN 1 Pontianak". The method used in this research was descriptiove in the form of a correlative study. The tools of data collection were questionnaire, observation sheets, interview guidance and documentation. The population of this research were154 year-11 accountancy studentsand 36 as the samples. The result of this research showed that learning environment in the school was in high category with 72,88%. The year-11 accountancy students' motivation to learn was also in high category with 77,88%. Based on the analysis data, there was a resemblance 33,,814+0,44x. Due to the high regression value, or (R) effect  was 0,583 which categorized as average.The result of t test showed that t value > t table was (5,596>2,001). Therefore Ha was acceoted and Ho was rejected, so that it could be conluded that the learning enfironment affected the motivation of year-11 accountancy students at "SMKN 1 Pontianak". Coefficient determination (R2) result was 0,339 which meant the contribution percentage of the environment learning effect at school toward the year- 11 accountancy students' motivation at "SMKN 1 Pontianak  was 33,9% meanwhile the rest was 66,1 % which affected with another factors such as: family and social environment. Keyword: School Learning Environment, Students Motivation to Learn, Accounting Major